2020
DOI: 10.2147/ott.s241818
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA FOXP4-AS1 Is Involved in Cervical Cancer Progression via Regulating miR-136-5p/CBX4 Axis</p>

Abstract: Introduction: Cervical cancer (CC) is a major health threat to women worldwide. Long non-coding RNA (lncRNA) has been reported to play crucial roles in regulating carcinogenesis, including CC. Methods: In this work, levels of lncRNA forkhead box P4 antisense RNA 1 (FOXP4-AS1) in CC cell lines and normal cell lines were analyzed with quantitative Real-Time Polymerase Chain Reaction (qRT-PCR) method. Effects of FOXP4-AS1 on CC cellular behaviors including proliferation, migration, and invasion were explored. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…Accumulating studies showed that lncRNAs can function as a ceRNA to regulate their target genes and then form a network in CC, such as OIP5-AS1/miR-448/Bcl-2 axis [33] and FOXP4-AS1/miR-136-5p/CBX4 axis [34]. Based on this, we supposed that ACTA2-AS1 might also regulate the target gene of miR-143-3p to exert its function.…”
Section: Discussionmentioning
confidence: 88%
“…Accumulating studies showed that lncRNAs can function as a ceRNA to regulate their target genes and then form a network in CC, such as OIP5-AS1/miR-448/Bcl-2 axis [33] and FOXP4-AS1/miR-136-5p/CBX4 axis [34]. Based on this, we supposed that ACTA2-AS1 might also regulate the target gene of miR-143-3p to exert its function.…”
Section: Discussionmentioning
confidence: 88%
“…Surgery, radiotherapy and chemotherapy for early cervical cancer have good effects, but in advanced stage, the therapeutic effect of metastatic and recurrent cervical cancer is very limited and the survival rate is low. [6][7][8][9][10] How to effectively treat advanced and recurrent cervical cancers is the hot spot of current research. In this study, we proved the correlation…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The invasion and metastasis of cervical cancers are the main cause of death in patients and lymphatic metastasis is one of the main poor prognosis of cervical cancers. [8][9][10] Therefore, that we further studied about biological processes of cervical cancer metastasis, and excavated the key regulatory factors and signal transduction network, and developed new therapeutic targets and strategies, and improved the survival rate of patients, has very important clinical significance. However, the mechanism of cervical cancer has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is crucial to identify and to investigate the function and mechanism of novel lncRNAs during the progression of MCL. lncRNA forkhead box P4 antisense RNA 1 (FOXP4-AS1) has been reported as an oncogene in multiple solid cancers, including osteosarcoma (11), prostate lncRNA FOXP4-AS1 predicts poor prognosis and accelerates the progression of mantle cell lymphoma through the miR-423-5p/NACC1 pathway cancer (12), colorectal cancer (13), esophageal squamous cell carcinoma (14) and cervical cancer (15). Nevertheless, the biological function and related mechanisms of FOXP4-AS1 in MCL remain to be uncovered.…”
Section: Introductionmentioning
confidence: 99%